Stronger connections: family stress, violence and mental health - Nazish Hussain Ali Pachani (International Journal on Women Empowerment, 2015)
Traditional family dynamics, with modernity, have evolved disorganization in intra-familial relationship. Family support and affection plays an important role in securing attachment between family members which results in; physical, social, mental and emotional well-being. Alterations have attributed crucial exacerbation of mental illness in society. In Pakistan 89.2% of women with depression and 89.5% of women with Post traumatic stress disorder (PTSD) reported physical and psychological violence in the family. To identify psychosocial risk factors in order to enhance victim’s quality of life. This case study was conducted in the period of October – December 2014 from various online databases such as PubMed, Cinahl, Medline and Google Scholar, and other relevant research articles ranging from 2009-2014. Family stress and violence is one of the key threats to individual mental health. Domestic violence often follows a cyclical pattern of abusive relationship which leads to mental illness. Encouraging relaxation exercises and strengthening social skill is significantly important to halt the deteriorating condition. Individual and group counselling session together with community based awareness platforms are the cornerstone options for the personalized and coordinated care. Public private partnership in short term and long term initiatives for empowerment would yield inspired individuals which in turn end up in inspired community. Genetic predisposition and stressful environmental conditions have a potential to deteriorate individuals mental health. Stress, violence, abuse, maltreatment is common in girls and in women who lives with foster families. Effective community participation is a way forward to weaken the connections between family stress, violence and mental illness from society.